2021
DOI: 10.46419/vs.52.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ectoparasites in free-range backyard chicken flocks in northeast Algeria

Abstract: Free-range backyard chicken breeding is gaining popularity in Algerian rural regions. Due to the natural rearing conditions, chickens are exposed a wide range of microbes and ectoparasites. Currently, little is known about the variety of ectoparasites infesting free-range chickens in Algeria. The present study was conducted over a two year period on 169 backyard chicken, with the aim of identifying and estimating the prevalence of ectoparasites on different body parts of the chickens, and their immediate envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(48 reference statements)
2
1
0
Order By: Relevance
“…The prevalence of ectoparasite infestation in females was 58.6%, which was slightly relatively high compared to the males that had a prevalence of 50.1%. Although the difference was not statistically significant, our study is in agreement with the study conducted by Nahal et al [19] , Sabuni et al [20] and Bala et al [5] . Our results are in disagreement with the study conducted by Mungube et al [21] who reported the higher prevalence of ectoparasites in males than females.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of ectoparasite infestation in females was 58.6%, which was slightly relatively high compared to the males that had a prevalence of 50.1%. Although the difference was not statistically significant, our study is in agreement with the study conducted by Nahal et al [19] , Sabuni et al [20] and Bala et al [5] . Our results are in disagreement with the study conducted by Mungube et al [21] who reported the higher prevalence of ectoparasites in males than females.…”
Section: Resultssupporting
confidence: 93%
“…M. gallinae has been reported in Nigeria by Bala et al [5] with a prevalence of 8.1% which is lower than our findings. Interestingly, Sadiq et al [26] reported the high prevalence which was 97.7% in Kashmir Valley and the recent study which was conducted in Algeria by Nahal et al [19] showed the high prevalence of 82.84%. Prevalence of 57.33% has been reported in Free-ranging Backyard Chickens of Sabzevar City, Iran, by Shamsi et al [27] .…”
Section: Resultsmentioning
confidence: 99%
“…Ten different species of arthropod belonging to two orders; Acarina (Argas persicus, Cnemidocoptes mutans and Ornithonyssus bursa) and Mallophaga (Menopon gallinae, Lipeurus caponis, Menacanthus stramineus, Goniodes gigas, Goniocotes gallinae and Columbicola columbae) were identified. The species of lice encountered in this study are similar to those earlier reported in chickens from Argentina (Nahal et al, 2021); Ethiopia (Mata et al, 2018), Nigeria (Chidiogo et al, 2020), and in chickens, turkeys and pigeons from Iran (Rezaei et al, 2016). Conversely, the poultry flea, Echidnophaga gallinacea, consistently reported in previous studies was not encountered in the current study.…”
Section: Discussionsupporting
confidence: 91%